2018
DOI: 10.3390/nu10111578
|View full text |Cite
|
Sign up to set email alerts
|

Regularity of Breakfast Consumption and Diet: Insights from National Adult Nutrition Survey

Abstract: Breakfast is considered to be one of the most important meals of the day. Its omission has been reported to be associated with increased disease risk, such as obesity, diabetes, and coronary heart disease, as well as unhealthy lifestyle and lower dietary quality. Using data from the National Adult Nutrition Survey (NANS)—a food consumption survey conducted among 1500 Irish men and women over 18 years of age, residing in the Republic of Ireland at the time the survey was conducted—we aimed to characterize break… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 30 publications
1
29
0
1
Order By: Relevance
“…Limited research has been published on chrono-nutrition in relation to dietary intakes and health outcomes in populations who do not perform shift work [43]. Nevertheless, previous studies in adolescents and (young) adults showed that regular breakfast consumption was associated with overall higher diet quality and skipping breakfast was associated with lower diet quality [42,44,45]. This is in line with the positive correlation found between DHD-index score and breakfast regularity in controls, suggesting a higher diet quality in controls who regularly consumed breakfast.…”
Section: Discussionmentioning
confidence: 99%
“…Limited research has been published on chrono-nutrition in relation to dietary intakes and health outcomes in populations who do not perform shift work [43]. Nevertheless, previous studies in adolescents and (young) adults showed that regular breakfast consumption was associated with overall higher diet quality and skipping breakfast was associated with lower diet quality [42,44,45]. This is in line with the positive correlation found between DHD-index score and breakfast regularity in controls, suggesting a higher diet quality in controls who regularly consumed breakfast.…”
Section: Discussionmentioning
confidence: 99%
“…The use of dietary quality as an arbiter of mealtime regularity was chosen because previous studies have suggested higher dietary quality with "regular" eating, especially breakfast [22,36,37], but mainly because of the recognition more than two decades ago that a measure of mealtime regularity needed to be tested against overall dietary quality [26] and that the need to examine how meal timing is related to dietary quality continues to be recommended [22]. Health status is also a potential comparator against a mealtime regularity index, especially given the newly proposed relationships between microbiota, single nucleotide polymorphisms of several genes and cellular circadian rhythms [14,15,[18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…There are several possible explanations for the observation of a relation between eating behaviors and grip strength. First, our primary hypothesis was that eating behaviors would exert a beneficial influence on muscle strength, as regular breakfast consumption would lead to higher nutrient intake [13] and higher energy intake [16]. Nutrient and energy intake is positively associated with muscle strength [27].…”
Section: Discussionmentioning
confidence: 99%
“…In a different study, self-reported eating rate is positively associated with the presence of metabolic syndrome in Japanese men and women [11]. Other studies have also shown that night eating can cause nutritional imbalance [12], and compared with irregular breakfast consumption, regular breakfast consumption contributes to higher nutrient intake, such as dietary fiber, iron, calcium, and folate [13]. As such, night eating and irregular breakfast consumption may contribute to muscle strength decrease owing to nutrient imbalance; indeed, nutrient deficiency is a well-known predictor of muscle strength loss [14].…”
Section: Introductionmentioning
confidence: 96%